FLC-based, PV-fed interleaved dual buck-boost converter for EV battery charging applications. Issue 4 (April 2022) - Krithiga, S.; Sujitha, N.; Sandeep, G.J.S.M.; Gokulnath, R.; Subudhi, Partha Sarathi
Abstract: Fuzzy logic controller is developed for PV array fed interleaved dual buck-boost (IDBB) converter for EV battery charging applications. The inner dynamics of the IDBB converter is improved using the damping network. Irrespective of the change in solar insolation conditions, the developed fuzzy logic controller adjusts the duty ratio of the converter to obtain constant output voltage. Simulation studies have been carried out using MATLAB/Simulink software and Fuzzy Logic Controller modelled in MATLAB/Simulink software was interfaced with dSPACE1103 to carry out the experimental investigation in Hardware-in-loop methodology in dSPACE workstation. The experimental results are on-par with the simulated results validating the proposed system. Abstract : Renewable energy, Electric vehicle battery charging system, Photovoltaic array, Fuzzy logic controller, Interleaved Dual Buck-Boost converter.